KEPUASAN ANGGOTA KOPERASI BERDASARKAN PENGARUH DARI CITRA KOPERASI DAN KUALITAS PELAYANAN - Mahardhika, Mustafidah; Arintowati, Dyan (Universitas Nusantara PGRI Kediri, 2022)
The purpose of this research is to determine if any or not the influence of cooperative image and service quality toward cooperative members satisfaction. This research method adopts a quantitative research method. Data collection techniques by interviewing, documenting, and providing questionnaires to cooperative members. Data analysis uses multiple linear regression analysis. This research provides a result that cooperative image and service quality partially affect cooperative members satisfaction. The results also show that cooperative image and service quality have a simultaneous effect on cooperative members satisfaction. The cooperative image has the greatest influence on the cooperative members satisfaction. It is so important to maintain the cooperative image remain positive, so that members feel satisfied. Maintaining the cooperative image is the same as maintaining the loyalty of members to entrust their every economic need to the cooperative.